Sensitivity analysis for overload-relief in transmission lines using an implicitly coupled method (CRIC) - Hoji, E. S. [UNESP]; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
The restructuring of energy markets to provide free access to the networks and the consequent increase of the number of power transactions has been causing congestions in transmission systems. As consequence, the networks suffer overloads in a more frequent way. One parameter that has strong influence on transfer capability is the reactive power flow. A sensitivity analysis can be used to find the best solution to minimize the reactive power flows and relief, the overload in one transmission line. The proposed methodology consists on the computation of two sensitivities based on the use of the Lc matrix from CRIC (Constant Reactive Implicitly Coupled) power flow method, that provide a set of actions to reduce the reactive power flow and alleviate overloads in the lines: (a) sensitivity between reactive power flow in lines and reactive power injections in the buses, (b) sensitivity between reactive power flow in lines and transformer's taps. © 2006 IEEE.
Keywords: Power Transmission Lines; Reactive Power Control; Sensitivity; Coupled method; Energy markets; Free access; In-line; matrix; Power flows; Power transactions; Reactive power flow; Reactive power injections; Transfer capability; Transmission line; Transmission systems; Electric lines; Electric power transmission; Sensitivity analysis; Transmission line theory; Reactive power